Compact dual L-slit slotted antenna for spacecraft, WLAN, Wi-Fi, and Bluetooth application - Basar, Md. Rubel; Hossain, Md. Abul; Hoque, Md. Reshad Ul; Morshed, Khaled Mahbub (2012 7th International Conference on Electrical and Computer Engineering, 2012)
In this paper a compact dual L-slit slotted microstrip antenna for entire unlicensed national information infrastructure (UNII) band (UNII low 5.15-5.25 GHz, UNII mid 5.25-5.35 GHz, UNII worldwide 5.47-5.725 GHz and UNII upper 5.725-5.825 GHz) is proposed. This compact (15 × 9 mm size) antenna has good characteristics to cover UNII band for 5.2 GHz WLAN, 5.5 GHz Wi-Fi and 5.8 GHz WLAN & Bluetooth operation. In addition it covers 2.7-2.8 GHz frequency band (∼95% bandwidth coverage) for spacecraft application. Coaxial feeding is used and analysis has been done using IE3D software. The antenna provides radiation efficiency, gain and VSWR are 93.41%, 6.5 dBi and 1.01 at 5 GHz frequency band and 48.09%, 1.8 dBi and 1.55 at 2.7 GHz frequency band respectively. Aside this the proposed antenna has accomplished the perfect impedance matching 49.41 Ω without any matching network.